My mobile class assistant application on android platform - Nurul Wahidah, Zainal Al Abidin (2013)
The exponential growth of information has made it important for learning to take place quickly. The emergence of ICT and the Internet has greatly influenced the way knowledge delivered. This has resulted in the development of learning management system. Here, the developer sees this sophisticated technology to help lecturers at the university to reduce their burdens in spreading the knowledge or announcements about their future class planning to students. This report presents brief detail of the project based for a task or event viewer via Android mobile application to be developed as part of University Malaysia Pahang (UMP) final year project. The aim of this project is to develop an Android-based mobile application that can provide information delivery from one device to another. This information could be an announcement, event, task or reminder. This project also aimed to establish connections of integrated databases of user’s information among UMP lecturers and students. This project is a project based on Android OS platform which enables the students to view the updated event of current subject taken on their smart phone. The content that lecturers post from their mobile application will be delivered to the student’s mobile application. The project was implemented in a small networking environment within FSKKP, UMP for the simulation testing purpose. Besides, there are two types of tool used for this project which are Eclipse SDK and WampServer. Eclipse SDK is used to run the source code of Android Java programming whereby WampServer is used to design the database of the project. The results from this project would be an integrated system which capable of receiving input from lecturers through the mobile application, manipulating the received data and outputting them to students in a graphical form via the mobile application installed on their smart phone. As a conclusion, this project provide benefits especially to the students as it will focused on preparing a to-do-list tasks which enables the students to manage their student life activities such as managing several tasks (quizzes, tests, assignments). With this application, we can learn to facilitate another way of communication among lecturers and students through the usage of new technology mobile environment on Android platform.